On a Cubically Convergent Iterative Method for Matrix Sign - Sharifi, M.; Karimi Vanani, S.; Khaksar Haghani, F.; Arab, M.; Shateyi, S. (The Scientific World Journal, 2015)
We propose an iterative method for finding matrix sign function. It is shown that the scheme has global behavior with cubical rate of convergence. Examples are included to show the applicability and efficiency of the proposed scheme and its reciprocal.